Use of photo methods in research studies with cancer survivors and their caregivers: a scoping review - Lanoye, Autumn; Cai, Lillian; Thomson, Maria D.; Hong, Susan (Journal of cancer survivorship, 2024)
Purpose Photo methods such as photo-elicitation and photovoice have traditionally been implemented as knowledge-generation techniques; however, they have also been conceptualized as tools for community impact and as interventions in and of themselves. We performed a scoping review to document how photo methods have been used in studies of cancer, to describe participant populations, and to identify opportunities for future directions for the use of photo methods in cancer. Methods An a priori search strategy was implemented across health-related databases with the following inclusion criteria: (1) study participants were diagnosed with cancer and/or were caregivers of those with cancer; (2) study participants were asked to take and/or respond to photographs as part of the study protocol; (3) articles were published in peer-reviewed journals; (4) articles were written in English. Results Eighty non-duplicative articles were identified; of these, 30 articles describing 24 individual studies were included for review. All but one (95.8%) of the studies utilized photovoice solely as a knowledge-generation technique without participant outcome measurement or analysis. Across all included studies, participants were largely women with breast cancer; other demographic and cancer-related variables (e.g., race and cancer stage) were not consistently reported. Caregivers were included in 37.5% of studies. Conclusion Photo methods are most frequently used in order to capture qualitative data in cancer populations; however, there are missed opportunities in their lack of use for intervention and systemic change. In addition, inconsistent reporting of demographics and cancer characteristics limits our ability to synthesize these data across studies.